Hypocholesterolemic effects of Kluyveromyces marxianus M3 isolated from Tibetan mushrooms on diet-induced hypercholesterolemia in rat - Xie,Yuanhong (2015)
To investigate the effects of Kluyveromyces marxianus M3 isolated from Tibetan mushrooms on diet-induced hypercholesterolemia in rats, female Wistar rats were fed a high-cholesterol diet (HCD) for 28 d to generate hyperlipidemic models. Hyperlipidemic rats were assigned to four groups, which were individually treated with three different dosages of K. marxianus M3+HCD or physiological saline+HCD via oral gavage for 28 d. The total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels in the serum and liver of the rats were measured using commercially available enzyme kits. In addition, the liver morphology was also examined using hematoxylin and eosin staining and optical microscopy. According to our results, the serum and liver TC, TG, LDL-C levels and atherogenic index (AI) were significantly decreased in rats orally administered K. marxianus M3 (p <0.01), and the HDL-C levels and anti atherogenic index (AAI) were significantly increased (p <0.01) compared to the control group. Moreover, K. marxianus M3 treatment also reduced the build-up of lipid droplets in the liver and exhibited normal hepatocytes, suggesting a protective effect of K. marxianus M3 in hyperlipidemic rats.